Faktor Penyebab Anak Menjadi Pelaku Kejahatan - Pertiwi; Lilik Andaryuni (Bulletin of Community Engagement, 2024)
The increasing involvement of children as perpetrators of crimes has become a serious concern in Indonesia. This study aims to analyse the factors contributing to juvenile delinquency using a juridical empirical approach. It examines three cases of children in conflict with the law involving acts of assault, sexual misconduct, and theft. The findings reveal that the primary factors influencing such behaviour include unstable family conditions, such as parental divorce and lack of parental attention, negative peer environments, and the adverse effects of technology, particularly easy access to pornographic content. Additionally, online gaming addiction significantly contributes to criminal behaviour, especially in theft cases. This study underscores the importance of family roles in moral education, supportive social environments, and monitoring the use of technology to prevent children from engaging in criminal acts. It recommends a holistic approach involving families, communities, and the government to address this issue. Effective interventions include strengthening family based education, enhancing digital literacy, and developing community based rehabilitation programs for children involved in criminal activities.